Community innovation for sustainable energy - Sabine Hielscher; Gill Seyfang; Adrian Smith (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2011)
As in other countries, there is a growing public, policy and business interest in the UK in the roles and potential of community-led initiatives for sustainable energy consumption and production. Such initiatives include green lifestyle-based activities to reduce energy consumption (e.g. Transition Towns, and Carbon Reduction Action Groups), more traditional behaviour change initiatives such as neighbourhood insulation projects and energy-saving campaigns, as well as renewable energy generation projects such as community-owned windfarms and biofuel projects. Case studies of specific projects identify a variety of rationales amongst participants, whilst policy interest suggests a more instrumental concern for facilitating additional, larger-scale sustainable energy transitions. Amongst participant rationales are ideas that bottom-up, community-based projects deliver energy savings and behaviour changes that top-down policy instruments cannot achieve, due to the greater local knowledge and engagement they embody, the sense of common ownership and empowerment, and the social capital and trust that is generated among local actors. These resources provide organisational and values-based 'grassroots innovations' which experiment with new consumption practices based on alternative 'new economics' values. However, previous research shows 'grassroots innovations' face a series of critical challenges requiring support to overcome, in order to achieve their potential benefits more widely. This includes developing 'niche' networks for mobilising reforms both to highly centralised energy institutions and infrastructures, as well as deeply ingrained social practices of 'normal' energy consumption and everyday life. What makes this experience fascinating for the purposes of the SCORAI workshop is the way these community-based initiatives are trying to develop new energy-related consumption practices with a view to the socio-technical transition to local, renewable or lower carbon energy systems. Understandably, many projects remain practically focused on securing early successes and resourcing their long-term survival. However, the institutional and infrastructure reforms that will help in this endeavour require strategies for addressing the wider (national and international) political economy of consumption which adopts an ecological modernisation approach to sustainability. In surveying the community energy scene in the UK, our paper pays particular attention to this last issue.
Keywords: 330; community; consumption; energy; innovation; sustainability transitions; Sustainable Development